SIMULATIONS TO SKILL ASSESSMENTS: AI TRANSFORMATIONS IN TVET" - Dr Roli Pradhan (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The integration of Artificial Intelligence (AI) in Technical and Vocational Education and Training (TVET) is transforming how skills are developed and assessed. AI-driven simulations and skill assessments are enhancing the learning experience, providing personalized learning pathways, and fostering a deeper understanding of complex vocational tasks. This paper explores the evolution of AI applications in TVET, focusing on the shift from traditional training methods to AI-enhanced simulations that replicate real-world environments. These AI-powered simulations allow learners to engage in hands-on training without the constraints of physical resources, enabling them to practice a wide range of skills in a safe, controlled, and cost-effective manner. Additionally, AI is revolutionizing skill assessments by offering real-time feedback, automating evaluation processes, and ensuring a more objective, data-driven approach to performance analysis. This transformation not only improves the accuracy of skill assessments but also provides learners with valuable insights into their progress, strengths, and areas for improvement. The paper discusses the implications of these innovations on TVET policy, curriculum design, and pedagogy, and highlights the potential of AI to bridge the gap between education and industry demands. It also addresses the challenges and opportunities in implementing AI-based solutions in TVET, aiming to create a more efficient and future-ready workforce.